2002
DOI: 10.1097/01.asn.0000025294.40179.e8
|View full text |Cite
|
Sign up to set email alerts
|

Early Initiation of Dialysis Fails to Prolong Survival in Patients with End-Stage Renal Failure

Abstract: Abstract. There is a trend to start dialysis earlier in patients with chronic renal failure. Studies that suggest improved survival from earlier initiation of dialysis are flawed in that they have measured survival from start of dialysis rather than from a time point before dialysis, when patients have the same renal function. This flaw is termed lead-time bias. Using the electronic patient record at the renal unit of Glasgow Royal Infirmary, all patients were identified who had received dialysis for chronic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
141
0
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 224 publications
(155 citation statements)
references
References 18 publications
10
141
0
4
Order By: Relevance
“…Since the previous survey on this matter in 2000, several debates and cohort studies were published suggesting that starting RRT at higher eGFRs may be harmful. [2][3][4][5][6]8,12,14,18,19,28 Therefore, we needed an update regarding current opinions on this topic.…”
Section: Most Frequently Mentioned Reasons As Basis For Opinion (% Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the previous survey on this matter in 2000, several debates and cohort studies were published suggesting that starting RRT at higher eGFRs may be harmful. [2][3][4][5][6]8,12,14,18,19,28 Therefore, we needed an update regarding current opinions on this topic.…”
Section: Most Frequently Mentioned Reasons As Basis For Opinion (% Ofmentioning
confidence: 99%
“…In addition, they were unable to assess clinical status or specific reasons to start RRT at a particular moment in time. [2][3][4][5] The IDEAL (Initiating Dialysis Early and Late) trial was the first randomized controlled trial attempting to assess whether starting dialysis therapy at high (10-14 mL/min/1.73 m 2 ) or low (5-7 mL/min/1.73 m 2 ) estimated glomerular filtration rates (eGFRs) is more beneficial with respect to patient survival. However, 76% of patients randomly assigned to start at low eGFRs actually started at higher levels because of uremic signs and symptoms, resulting in a relatively small difference in eGFRs between the groups.…”
mentioning
confidence: 99%
“…Despite the weak evidence, early initiation was accepted and it was common practice until recently. More recent studies, including a randomized controlled trial, did not support early initiation of dialysis in CKD patients [5,8,9,12,[15][16][17][18]. The large multicenter trial from Netherland, the Netherlands Cooperative Study on the Adequacy of Dialysis, was the first observational study which casts doubt on the advantages of early dialysis initiation [7].…”
Section: Discussionmentioning
confidence: 99%
“…In 2003, Beddhu et al [9] reported that higher eGFR was associated with higher risk of death, but in a subgroup of patients with measured creatinine clearance, there was no association with mortality. Traynor et al [8], on the other hand, reported that higher creatinine clearance at initiation of dialysis was associated with elevated mortality risk. The largest observational study from the USA found a dose-dependent increase in mortality associated with earlier dialysis initiation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation